1997
DOI: 10.1074/jbc.272.31.19429
|View full text |Cite
|
Sign up to set email alerts
|

α4 Integrin Binding Interfaces on VCAM-1 and MAdCAM-1

Abstract: Integrins are a family of heterodimeric adhesion receptors that mediate cellular interactions with a range of matrix components and cell surface proteins. Vascular cell adhesion molecule-1 (VCAM-1) is an endothelial cell ligand for two leukocyte integrins (␣4␤1 and ␣4␤7). A related CAM, mucosal addressin cell adhesion molecule-1 (MAdCAM-1) is recognized by ␣4␤7 but is a poor ligand for ␣4␤1. Previous studies have revealed that all ␣4 integrin-ligand interactions are dependent on a key acidic ligand motif cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
71
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 54 publications
2
71
0
Order By: Relevance
“…Such a mechanism has been proposed for the binding of the ␣ 5 ␤ 1 integrin to fibronectin, where the RGD sequence in the tenth type III repeat together with a "synergy region" in the ninth type III repeat contribute to integrin binding (82). Similarly, along with the critical CDloop in domain 1 of VCAM-1 and MAdCAM-1, an "accessory site" in domain 2 has been implicated in the binding of the ␣ 4 ␤ 1 and ␣ 4 ␤ 7 integrins (9,(83)(84)(85). For these non-A-domain-containing integrins, it is interesting that although the primary binding site in the ligand includes a critical exposed acidic residue, the accessory site need not.…”
Section: Discussionmentioning
confidence: 99%
“…Such a mechanism has been proposed for the binding of the ␣ 5 ␤ 1 integrin to fibronectin, where the RGD sequence in the tenth type III repeat together with a "synergy region" in the ninth type III repeat contribute to integrin binding (82). Similarly, along with the critical CDloop in domain 1 of VCAM-1 and MAdCAM-1, an "accessory site" in domain 2 has been implicated in the binding of the ␣ 4 ␤ 1 and ␣ 4 ␤ 7 integrins (9,(83)(84)(85). For these non-A-domain-containing integrins, it is interesting that although the primary binding site in the ligand includes a critical exposed acidic residue, the accessory site need not.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these proteins contains putative integrin binding sequences in the linker between ␤ strands C and D that is at the position of the IDSPL sequence in modules 1 and 4 of human VCAM-1 (55). Integrins ␣M␤2 (56) and ␣L␤2 (57) contain an I domain in the ␣ subunit.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have revealed that some residues in MAdCAM-1 are important for MAdCAM-1-␣ 4 ␤ 7 binding (9,12,13,15), the structural basis for supporting MAdCAM-1-␣ 4 ␤ 7 -mediated rolling and firm cell adhesion remains elusive because the static cell adhesion assay used in those studies is unable to distinguish rolling and firm cell adhesion. In this study, we used a flow chamber assay to screen the critical residues in MAdCAM-1, which are important for supporting rolling and firm cell adhesions, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…The essential integrin-binding motif (LDTS) resides in the CCЈ loop of MAdCAM-1 D1, and the Asp-42 in the LDTS motif serves as the primary ␣ 4 ␤ 7 -binding site by directly interacting with the metal ion at the metal ion-dependent adhesion site (MIDAS) in the integrin ␤ 7 I domain (8,(12)(13)(14). Mutational studies suggest that some other residues in the CCЈ loop of MAdCAM-1 are also involved in MAdCAM-1-␣ 4 ␤ 7 binding (9,12,13). The DE loop in D2 is predominated by negatively charged residues, which have been reported to play an important role in determining integrin binding specificity (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation